Annotated checklist of Orthoptera of the Maltese Islands - Cassar, Louis F; Ebejer, Martin J; Massa, Bruno (Zootaxa, 2020)
The representation in the Maltese Islands of the Order Orthoptera, including the Tettigonioidea, Grylloidea, Gryllotalpoidea, Tetrigoidea, Pyrgomorphoidea and Acridoidea, is reviewed for the first time in almost fifty years. A total of fifty-five species are treated, of which forty-six are accepted and nine are rejected on the basis of re-evaluated taxonomic evidence, including the re-examination of actual specimens from historical collections, and consideration of species’ distribution. Two species, namely, Platycleis sabulosa Azam, 1901 and Oecanthus dulcisonans Gorochov, 1993, are reported for the first time from the Maltese Islands. Of the confirmed taxa, the occurrence of three species, Oedipoda caerulescens caerulescens (Linnaeus, 1767), Sphingonotus obscuratus lameerei Finot, 1902, and Sphingonotus savignyi savignyi Saussure, 1884, is considered accidental and another species, Schistocerca gregaria gregaria (Forskål, 1775), is known for its dependence on episodes of passage from the African mainland, while the status of another four taxa remains unclear. Extirpation of some of the rare and localised species, such as Conocephalus conocephalus (Linnaeus, 1767), Ruspolia nitidula (Scopoli, 1786), Brachytrupes megacephalus (Lefebvre, 1827), and Heteracris adspersa (Redtenbacher, 1889), is not excluded unless appropriate conservation measures are introduced and implemented.